On Some Methodological Problems of Ethnopsychology - Sargsyan, Armenuhi
Ուսումնասիրությունը նվիրված է էթնիկ հոգեբանության՝ որպես գիտության ճյուղի ուսումնասիրության մեթոդաբանությանը, որի առարկան ժողովուրդների էթնոհոգեբանական բնութագրերն են իրենց ողջ բազմազանությամբ։ The object of study of ethnic psychology as a branch of science is the ethnopsychological characteristics of peoples in all their diversity. Methods and materials: The historical-comparative method considered a whole range of parameters - historical, environmental, cultural, socio-economic in any possible combination. Analysis: At the level of general methodology, the general patterns of development of ethnopsychology are considered and studied. Results: The level of specific methodology is understood in ethnopsychology as a means of studying some aspects of science: the level of private methodology as research and analysis using various methods of specific phenomena studied by ethnopsychology. Объектом изучения этнопсихологии как отрасли науки являются этнопсихологические особенности народов во всем их мно- гообразии. Методы и материалы: Историко-сравнительным методом рассмотрен целый комплекс параметров – исторических, экологических, культурных, социально-экономических в любых возможных сочетаниях. Анализ: На уровне общей методологии рассматриваются и изучаются общие закономерности развития этнопсихологии. Результаты: Уровень специфической методологии понимается в этнопсихологии как средство изучения некоторых аспектов науки: уровень частной методологии как исследования и анализа с использованием различных методов конкретных явлений, изучаемых этнопсихологией.
Keywords: Psychology